Start-up propulsion biomechanics changes with fatiguing activity in persons with spinal cord injury - Bossuyt, Fransiska M. (J Spinal Cord Med, 2019)
Objective: Shoulder pathology is a common condition in wheelchair users that can considerably impact quality of life. Shoulder muscles are prone to fatigue, but it is unclear how fatigue affects start-up propulsion biomechanics. This study determines acute changes in start-up wheelchair propulsion biomechanics at the end of a fatiguing propulsion protocol. Design: Quasi-experimental one-group pretest-postest design. Setting: Biomechanics laboratory. Participants: Twenty-six wheelchair users with spinal cord injury (age: 35.5 ± 9.8 years, sex: 73% males and 73% with a paraplegia). Interventions: Protocol of 15 min including maximum voluntary propulsion, right- and left turns, full stops, start-up propulsion, and rests. Outcome measures: Maximum resultant force, maximum rate of rise of applied force, mean velocity, mean fraction of effective force, and mean contact time at the beginning and end of the protocol during start-up propulsion. Results: There was a significant reduction in maximum resultant force (P < 0.001) and mean velocity (P < 0.001) at the end of the protocol. Also, contact time was reduced in the first stroke of start-up propulsion (P < 0.001). Finally, propelling with a shorter contact time was associated with a greater reduction in performance (maximum velocity) at the end of the protocol. Conclusion: There are clear changes in overground propulsion biomechanics at the end of a fatiguing propulsion protocol. While reduced forces could protect the shoulder, these reduced forces come with shorter contact times and lower velocity. Investigating changes in start-up propulsion biomechanics with fatigue could provide insight into injury risk.